Evaluation of the effects of conservation tillage on field crops productivity and profitability in the Gezira Scheme, Sudan - A. El-Awad, Sheikh El Din; Babiker, Sara (Gezira Journal of Agricultural Science; Vol 13 No 1 (2015), 2015)
A permanent experimental site at Gezira Research Station Farm was chosen for five consecutive years (2004/05 to 2008/09), to represent the Gezira Scheme crops rotational serial, which is cotton, wheat, groundnut, sorghum and fallow. The objective was to evaluate the effects of conservation tillage (continuous reridging) on crop productivity and profitability compared to conventional tillage practices for each crop. Each crop was sown with the use of the two tillage systems of land preparation with three replicates. Crops were manually sown using the recommended seed rate, where wheat sowing was done on the top of 80-cm beds in three rows 15-cm apart. The soil bulk density and the corresponding soil moisture content were determined for each crop after the first irrigation(at seedling stage) and at flowering stage at three soil depths. The results indicated no significant differences between the two tillage systems for all crops measured traits. Conservation tillage was found to reduce the cost of production of all the rotational crops in comparison with conventional practices. Accordingly, conservation tillage could be adopted for field crops production in the irrigated schemes located in the Sudan clay plains, provided that the fields are free from perennial weeds and not compacted. تم اختيار موقع دائم في مزرعة محطة بحوث الجزيرة لمدة خمسة سنوات متتالية (2004/05 إلى 2008/09)، وذلك لتمثيل مسلسل الدورة الزراعية للمحاصيل بمشروع الجزيرة، وهو القطن، القمح، الفول السوداني، الذرة والبور. كانت الأهداف لتقييم آثار الحراثة الحافظة(فتح السراب المستمر) على إنتاجية وربحية المحصول بالمقارنة مع عملية الحراثة السائدة لكل محصول. تمت زراعة كل محصول باستخدام نظامي الحراثة لتحضير الأرض بثلاثة مكررات. كان حجم المربع المزروع 10م×10 م، والمساحة المحصودة 3.2م×5م (4 صفوف×5م). تمت زراعة المحاصيل بمعدل كمية التقاوي الموصي بها يدوياً. وقد تم بذر القمح على قمة مساطب 80 سم بتأسيس ثلاثة صفوف على بعد 15 سم من بعضها البعض. تم تحديد الكثافة الظاهرية للتربة ومحتوى الرطوبة المقابل لها لكل محصول بعد الرية الأولى و في مرحلة الإزهار. أوضحت النتائج عدم وجود فروقات معنوية بين نظامي الحراثة بالنسبة لكل الصفات المقاسة لجميع المحاصيل. كما وجد أن الحراثة الحافظة قد قللت تكلفة الإنتاج مع توفير كبير في تكلفة نظام الحراثة للهكتار بالمقارنة مع ممارسة الحراثة السائدة لكل محاصيل الدورة. وعليه، فيمكن تبني الحراثة الحافظة (فتح السراب المستمر) لإنتاج المحاصيل الحقلية بالمشاريع المروية التي تقع في سهول السودان الطينية، شريطة أن تكون الحقول خالية من الحشائش المعمرة وغير متصلبة.